2020
DOI: 10.1248/bpb.b19-00901
|View full text |Cite
|
Sign up to set email alerts
|

circACTR2: A Novel Mechanism Regulating High Glucose-Induced Fibrosis in Renal Tubular Cells <i>via</i> Pyroptosis

Abstract: Diabetic kidney disease (DKD) is the leading cause of chronic kidney disease. Current therapies for DKD are insufficient. Therefore, there is an urgent need for identifying new therapies. An increasing number of micro RNAs (miRNAs) and long noncoding RNAs (lncRNAs) have been demonstrated to modulate the progression of diabetic kidney disease. Nevertheless, until now, there have been few reports evaluating the relevance of circular RNAs (circRNAs) in DKD. circRNAs have been reported to regulate the occurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…Knockout of circACTR2 significantly inhibited high-glucose–induced IL-1β release, and the production of collagen IV and fibronectin in HK-2 cells. By clarifying the role of circRNAs in the renal tubular cell pyroptosis-related inflammasome, new insights into the pathogenesis and treatment strategies of DKD may be attained ( 121 ). Li et al.…”
Section: Correlation Of the Pyroptosis-related Inflammasome Pathway Wmentioning
confidence: 99%
“…Knockout of circACTR2 significantly inhibited high-glucose–induced IL-1β release, and the production of collagen IV and fibronectin in HK-2 cells. By clarifying the role of circRNAs in the renal tubular cell pyroptosis-related inflammasome, new insights into the pathogenesis and treatment strategies of DKD may be attained ( 121 ). Li et al.…”
Section: Correlation Of the Pyroptosis-related Inflammasome Pathway Wmentioning
confidence: 99%
“…Wen et al have reported that circACTR2 knockdown inhibits pyroptosis and reduces IL-1β secretion in HG-stimulated fibrosis in renal tubular cells. 183 The authors have detected a new circRNA, circACTR2, that modulates HG-stimulated fibrosis, inflammation, and pyroptosis in proximal tubular cells. Therefore, targeting the circRNAs can serve unique insight regulating pyroptosis into DN’s pathogenesis and create a novel therapeutic strategy in the future.…”
Section: Targeting Inflammasome and Pyroptosis For The Therapeutic Implications Of Diabetic Complicationsmentioning
confidence: 99%
“…Notably, with the research trends of epigenetics, the gene therapy of IL-22 and some types of long-non coding RNA (lncRNA) also perform great effects on inhibiting renal cell pyroptosis and, thus, attenuating kidney fibrosis and DKD progression [ 15 , 18 , 32 , 132 , 133 ].…”
Section: Therapeutic Drugs Targeting Pyroptosis For Dkd Treatmentmentioning
confidence: 99%